Isolation and Identification of Thermophiles Bacteria from one of the Hottest Places on the Planet (Lut Desert, Iran) and Measuring their Enzyme Activities. Issue 10 (2nd November 2021) - Shahsavari, Nemat; Kafilzadeh, Farshid; Kargar, Mohammad
Abstract: More than 70% of heat resistance enzymes, such as lipase, cutinase, cellulase, Alpha amylase, L-aspartas, are being used in industries which are producing by thermophillic microorganisms. The purpose of this research is Isolation, molecular identification of thermophillic bacteria from the soil of hotest area in Iran and measuring extracellular enzymes activities and kinetics. According to the sampling principles, taking sample from the soil is done from the 5 cm depth of the soil and it became isolated and identified by using ribotyping stub. According to standard methods, the enzyme activities of isolated stub were measured and analyzed. Licheniformis was identified in in ribotyping of the isolated sample. This bacterium had produced the highest amount of cellulase which was 17.5 u/ml, after 72 hours, while pH was equal to 8. As well, the highest amount of protease production was done under alkaline conditions. The asparaginase and lipase activity levels in the isolated Bacillus licheniformis are 4 and 19 enzyme units per ml respectively at 55 °C, while pH is equal to 8. Bacillus licheniformis strain extracted from Gandome Beryan area is an appropriate source of heat-resistant extracellular enzymes with suitable enzyme activity level which can be used in various industries.